Microstructure and nonlinear properties of Zn-V-Mn-Nb-O varistor ceramics with Nd2O3 substitution - Azis, Raba'ah Syahidah; Zakaria, Azmi; Abdullah, W. R. W.; Isa, N. H. (National Institute R and D of Materials Physics, 2017)
An abnormal grain growth of the ZnO-based ceramics due to highly reactive vanadium liquid phase disrupts its nonlinear properties. The effect of Nd2O3 concentration from 0.01 to 0.05 mol% on microstructure and electrical properties of ZnO-based varistor ceramics were investigated. The sample was fabricated via solid state method and sintered at 900 °C for 2 h. XRD analysis shows the V2O5 and Zn2Nb2Mn2O9 phase formation. SEM analysis shows the grain is more uniform and enlarged to 3.54 μm with Nd2O3 addition up to 0.03 mol%. Nd2O3 also increased both the nonlinear coefficient α and the breakdown electric field, E1mA to an optimum of 9.94 and 75 V/mm. Beyond that concentration, oxygen O vacancy formed at the grain boundary and diminished the electrical properties.